Evaluation of potassium formate as a potential modifier ofTEG for high performance natural gas dehydration process - Isa, Muhammad Aimen (Elsevier, 2013)
Triethylene glycol (TEG) is one of the most effective sorbents for natural gas dehydration. There are many processesusing this approach but none of them can combine high performance and economical energy consumption. In thisstudy hydrocarbon–water phase behavior was investigated for different TEG concentrations in different natural gasdehydration processes. The equilibrium correlations were investigated for predicting water dew point as a functionof TEG concentration. The effect of TEG concentration on the outlet gas dew point was also determined using phaseenvelope diagrams. The results showed that the (DRIZO) process achieved the most significantly reduces water dewpoint followed by conventional stripping gas dehydration process. Moreover, TEG was modified using potassiumformate as additive. The results showed that the absorption capacity of the modified TEG was improved, that isalmost duplicated. This modification augments the performance of the proposed mixture which can be potentiallyapplied to a real scale process.